Intermittent theta burst stimulation enhances prefrontal activation and connectivity: evidence from fNIRS - Zhao, Yi-ning; Zhang, Xing-yu; Huang, Ying-ying; Wu, Ji-chun; Bi, Xia (Frontiers in Human Neuroscience, 2025)
ObjectiveTo investigate the neuro-regulatory mechanisms of intermittent theta burst stimulation (iTBS) on prefrontal brain function.MethodsFunctional near-infrared spectroscopy (fNIRS) was used to monitor the blood flow dynamics response in the prefrontal cortex of 20 healthy adults. Measurements were taken at five time points (10, 25, 40, 55, and 70 min) after iTBS stimulation, as well as before stimulation (T0). The activation intensity of prefrontal cortex was assessed by quantifying the relative change in oxygenated hemoglobin concentration (β value), and functional connectivity between prefrontal-related brain regions was evaluated by calculating the correlation coefficients of oxygenated hemoglobin concentration between channels across time series for each subject.ResultsCompared with the pre-stimulation period, the activation intensity in the prefrontal cortex was significantly higher from 10 to 70 min after iTBS stimulation. Specifically, seven channels showed statistically significant differences, with peak effects occurring 10 min after intervention and gradually attenuating over time. Additionally, compared with T0, the functional connectivity (FC) strength of the prefrontal network was markedly enhanced 10 min after intervention, accompanied by a notable increase in the number of connections between channels. However, the FC strength gradually weakened over time, and no statistically significant differences in FC strength were observed at 55 and 70 min post-intervention. Taken together, We conclude that the neural modulation effects of a single iTBS session persist for ~40 min. These results elucidate the regulatory effects of iTBS intervention on brain functional activity from the perspective of brain functional connectivity, providing reference and evidence for the clinical application of iTBS.